Upaya Meningkatkan Hasil Belajar Siswa Kelas 4 Dengan Menggunakan Model Pembelajaran Discovery Learning Pada Mata Pelajaran IPA di SD Negeri Luworo 02 Kab Madiun - Retno Hartatik; WiWik Widiyaningsih; Dwi Rohman Soleh (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
This study aims to find out the low student learning outcomes in classroom learning with science content in class IV SD Negeri Luworo 02 Madiun Regency. By looking at the low learning outcomes of students who are still below the mark below the KKM, researchers will apply a learning model that can improve student learning outcomes. By applying discovery learning learning can make one of the basics in improving student learning outcomes to increase above the KKM. Based on the research method conducted by this researcher using a descriptive method which refers to Classroom Action Research. In the mid semester 1 test which included science learning was unsatisfactory at KKM 75. Out of 16 students The accuracy of the scores obtained reached 31.81% with a total of 6 students, while students who did not complete reached 68.18% or as many as 10 students with an average score of 66.5 in science content. And there was an increase in the first cycle with a percentage value of 63.7% and it increased in the second cycle, namely 90.9%. .